Sistem Informasi Penilaian Kinerja Dosen Dengan Metode Extreme Programming (Studi Kasus: STMIK MDP) - Desy Iba Ricoida; Denny Denny; Solihin Santoso (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Lecturer performance assessment is an activity carried out to evaluate the performance of lecturers with the aim of improving the performance of lecturers. On the process calculating assessment which is conducted by STMIK MDP it is still semi-computerized which causes the calculation of values take a long time, from lecture side there is no transparency information which explain source from calculating and the low aspect from that lecture. So it is need Lecturer performance assessment Systems that allows rapid calculation of values and provides information for monitoring lecture performance. . In making of this system, it using the Extreme Programming Methods because the assessment system of lecture performance is needed in a fast time while there are system requirements that are still changing, and for the system, we use an supporting application which is Atom and MySQL as an database. The result of design is an system that can processlecturer performance data quickly, provide performance information to lecturer and the vice director so that can help in decision-making related lecturer development.